Pengaruh Evaluasi Kinerja, Kompensasi Kinerja, Beban Kerja Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervening Pada KPP Pratama Pare - Aswahyuddin H; Arisyahidin Arisyahidin; Sriwahyuni Mega Hastuti (Otonomi, 2023)
This research aims to analyze the influence of work evaluation on motivation., the influence of work compensation on performance motivation, the influence of workload on performance motivation, analyzing the influence of motivation on performance. The influence of work evaluation, work compensation and workload through work motivation influences the performance of KPP Pratama Pare employees. This type of research is quantitative, with the results of the analysis showing that the performance evaluation variable has a significant effect on the work motivation of the Pratama Pare Tax Office employees. This can be interpreted as if the performance evaluation is good, then the performance of the Pare Pratama Tax Office employees will increase. The research sample used in the research was 50 employees of the Pratama Pare Tax Office using path analysis.